Going beyond nutrition: Regulation of potassium homoeostasis as a common denominator of plant adaptive responses to environment - Anschütz, Uta; Becker, Dirk; Shabala, Sergey (Journal of plant physiology, 2014)
Partially and fully completed plant genome sequencing projects in both lower and higher plants allow drawing a comprehensive picture of the molecular and structural diversities of plant potassium transporter genes and their encoded proteins. While the early focus of the research in this field was aimed on the structure–function studies and understanding of the molecular mechanisms underlying K+ transport, availability of Arabidopsis thaliana mutant collections in combination with micro-array techniques have significantly advanced our understanding of K+ channel physiology, providing novel insights into the transcriptional regulation of potassium homeostasis in plants. More recently, posttranslational regulation of potassium transport systems has moved into the center stage of potassium transport research. The current review is focused on the most exciting developments in this field. By summarizing recent work on potassium transporter regulation we show that potassium transport in general, and potassium channels in particular, represent important targets and are mediators of the cellular responses during different developmental stages in a plant's life cycle. We show that regulation of intracellular K+ homeostasis is essential to mediate plant adaptive responses to a broad range of abiotic and biotic stresses including drought, salinity, and oxidative stress. We further link post-translational regulation of K+ channels with programmed cell death and show that K+ plays a critical role in controlling the latter process. Thus, is appears that K+ is not just the essential nutrient required to support optimal plant growth and yield but is also an important signaling agent mediating a wide range of plant adaptive responses to environment.